Effect of Reduced Rates of N, P and K on the Yield of Rice (Oryza sativa L.) and its Nutrient Uptake (The Agriculturists, 2010)
An experiment was conducted to study the yield response and nutrient uptake of rice (BRRI dhan30) to reduced rates of N, P and K from the recommended fertilizer doses (RFD). The experiment was laid out in a randomized complete block design with four replicates. There were ten treatments viz. T1 (control), T2 (RFD), T3 (RFD - 20% N), T4 (RFD - 40% N), T5 (RFD - 20% P), T6 (FRD - 40% P), T7 (RFD - 20% K), T8 (RFD - 40% K), T9 (RFD - 20% NPK) and T10 (RFD - 40% NPK). The recommended fertilizer doses of the crop were 100 kg N, 20 kg P, 40 kg K, 20 kg S and 3 kg Zn ha-1. The highest grain yield (5.10 t ha-1) and straw yield (7.02 t ha-1) were obtained by applying recommended doses of fertilizers which were insignificantly different from those observed in the treatments where N, P and K were reduced at the rate of 20% from the recommended doses. Similar results were also found in case of P, K and S content and uptake by rice plant, while the variation for N was found significant. Overall results indicated that 20% reduction of either N or P or K from the recommended doses would not significantly affect the yield of rice.